2020
DOI: 10.1039/c9ra10031h
|View full text |Cite
|
Sign up to set email alerts
|

A biocompatible PAA-Cu-MOP hydrogel for wound healing

Abstract: PAA-Cu-MOP hydrogel prepared by a facile mixing and ultrasonic procedure showed an excellent wound healing behavior which was better than that of commercial recombinant human epidermal growth factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…In addition, the CP@Tf-hy, which can adhere to the hemorrhage position, can quickly construct a physical barrier to prevent wound bleeding . Moreover, the Cu ions on the hydrogel may also contribute to the hemostatic ability because Cu ions have procoagulant capacity …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the CP@Tf-hy, which can adhere to the hemorrhage position, can quickly construct a physical barrier to prevent wound bleeding . Moreover, the Cu ions on the hydrogel may also contribute to the hemostatic ability because Cu ions have procoagulant capacity …”
Section: Resultsmentioning
confidence: 99%
“…61 Moreover, the Cu ions on the hydrogel may also contribute to the hemostatic ability because Cu ions have procoagulant capacity. 62 Together, we propose that CP@Tf-hy eliminates bacteria through the following mechanisms: (i) In an acidic bacterial microenvironment, the CP@Tf-hy can generate •OH by the Fenton reaction of copper ions and self-supplied H 2 O 2 to damage bacteria. (ii) The CP@Tf-hy can release Cu 2+ to deplete GSH, and then, the produced Cu + induces an enhanced Fenton reaction with self-supplied H 2 O 2 from CP@Tf NPs and the endogenous H 2 O 2 in bacteria.…”
Section: 7mentioning
confidence: 96%
“…After testing, PaA-Cu-MOP hydrogel can promote cell proliferation and blood vessel generation, up-regulate cytokines, and even outperform recombinant human epidermal growth factors. Therefore, PaA-Cu-MOP hydrogel has excellent biocompatibility and can accelerate wound healing [ 99 ].…”
Section: Performance Of Antibacterial Hydrogelsmentioning
confidence: 99%
“…[4,7,8] Owing to their intriguing structures and their potential for a variety of applications, MOP have recently attracted considerable attention such as biomedicine, [9][10][11][12] catalysis, [7,[12][13][14] molecular sensing, [16] gas adsorption [17][18][19] and drug delivery. [20,21] Inspired by the superior performance of copper complexes in catalyzing oxidation ability in nature, our group have reported that Cu-MOP display excellent peroxidase mimicking enzyme activity in the physiological pH environment and were widely utilized in biosensing, [22] antibacterial [23] and cell protection [24] in recent years.…”
Section: Introductionmentioning
confidence: 99%